Negotiating space through names: A linguistic landscape perspective on toponymic practices in Shah Alam, Selangor: Konsep penamaan ruang publik di Malaysia: Studi Lanskap Linguistik - Qulub, Muhammad Farihul; Hamidi, Saddam Reza; Fika Burhan Tajalla (Al-Lisan: Jurnal Bahasa, 2025)
Background: Language plays a vital role in human interaction and has evolved beyond direct communication to convey messages through public spaces, known as the Linguistic Landscape (LL). The presence of LL varies across regions, from being highly visible to nearly absent. Aims: This study aims to analyse the conceptual and functional aspects of public space naming in Shah Alam, Selangor, using a linguistic landscape approach to understand how language shapes identity and social function in urban settings, employing a landscape linguistics perspective. Methods: This study used a qualitative descriptive method, where researchers directly describe the concept of naming in public space in Shah Alam city, Selangor, Malaysia, using the theoretical framework of Linguistic Landscape. The data were collected through direct field observation without involving interviews or informants. The analysis process involved data reduction, categorisation, contextual interpretation, and inductive drawing of conclusions. Visual triangulation and comparative site observation were employed to enhance the validity of the data. Results: The findings in this research reveal that the naming of public spaces can be classified based on informational functions. Symbolically, street naming reflects dynamics of power, cultural relationships, and language policy; office signage indicates aspects of language policy and status, while public signs expose elements of linguistic imperialism. The collected data include diverse types of linguistic signage: three instances of street naming, one city motto, two public information boards, two examples of office naming, two prohibition signs in public transport, and two signs designated for specific user groups. Implications: The implications of this research are twofold. Theoretically, these findings enrich the study of Linguistic Landscape. Practically, they offer insights into language planning and naming policies in multilingual public spaces.